If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + 12) = 5x Reorder the terms: (1 + x)(x + 12) = 5x Reorder the terms: (1 + x)(12 + x) = 5x Multiply (1 + x) * (12 + x) (1(12 + x) + x(12 + x)) = 5x ((12 * 1 + x * 1) + x(12 + x)) = 5x ((12 + 1x) + x(12 + x)) = 5x (12 + 1x + (12 * x + x * x)) = 5x (12 + 1x + (12x + x2)) = 5x Combine like terms: 1x + 12x = 13x (12 + 13x + x2) = 5x Solving 12 + 13x + x2 = 5x Solving for variable 'x'. Reorder the terms: 12 + 13x + -5x + x2 = 5x + -5x Combine like terms: 13x + -5x = 8x 12 + 8x + x2 = 5x + -5x Combine like terms: 5x + -5x = 0 12 + 8x + x2 = 0 Factor a trinomial. (6 + x)(2 + x) = 0Subproblem 1
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-6, -2}
| 3p-7p+14= | | -350=-7(8p-6) | | z-(-2)=6 | | 1=2(g-8)-1 | | 7x-10=-52 | | -4b+3(2x-5)=31 | | 2s-2s+2s-2=10 | | 5+(-9)= | | 4y-8=2y+10 | | 16x-4=38x+84 | | 4x+9x-5=0 | | 12r-8-12=0 | | 8x+34=2 | | 8z+3=9z-2z | | 4s+20=54 | | 5x+13=68 | | Ax=1 | | 8t+t-8t=7 | | 3y=(95636+18) | | 8x+7=3x-3 | | 19m-14m=20 | | -4(t-3)-(t+7)=5 | | x+4-4+2x=14 | | X-a=0 | | 8q-16-13q-3=-19 | | -4a+4+5a=13-26 | | xe+y=1 | | 10-k=9 | | 4=3(k+9)-1 | | 14c-1c=-21+3 | | 10y=4y+6+5y | | 6(3z-1)-2(z+9)=9(z+1) |